Impaired Embryonic Development in Mice Overexpressing the RNA-Binding Protein TIAR - Kharraz, Yacine; Salmand, Pierre-Adrien; Camus, Anne; Auriol, Jacques; Gueydan, Cyril; Kruys, Véronique; Morello, Dominique (PLOS ONE, 2010)
Background TIA-1-related (TIAR) protein is a shuttling RNA-binding protein involved in several steps of RNA metabolism. While in the nucleus TIAR participates to alternative splicing events, in the cytoplasm TIAR acts as a translational repressor on specific transcripts such as those containing AU-Rich Elements (AREs). Due to its ability to assemble abortive pre-initiation complexes coalescing into cytoplasmic granules called stress granules, TIAR is also involved in the general translational arrest observed in cells exposed to environmental stress. However, the in vivo role of this protein has not been studied so far mainly due to severe embryonic lethality upon tiar invalidation. Methodology/Principal Findings To examine potential TIAR tissue-specificity in various cellular contexts, either embryonic or adult, we constructed a TIAR transgenic allele (loxPGFPloxPTIAR) allowing the conditional expression of TIAR protein upon Cre recombinase activity. Here, we report the role of TIAR during mouse embryogenesis. We observed that early TIAR overexpression led to low transgene transmission associated with embryonic lethality starting at early post-implantation stages. Interestingly, while pre-implantation steps evolved correctly in utero, in vitro cultured embryos were very sensitive to culture medium. Control and transgenic embryos developed equally well in the G2 medium, whereas culture in M16 medium led to the phosphorylation of eIF2α that accumulated in cytoplasmic granules precluding transgenic blastocyst hatching. Our results thus reveal a differential TIAR-mediated embryonic response following artificial or natural growth environment. Conclusions/Significance This study reports the importance of the tightly balanced expression of the RNA-binding protein TIAR for normal embryonic development, thereby emphasizing the role of post-transcriptional regulations in early embryonic programming.